Perancangan Dan Implementasi Website Healthdoc Sebagai Produk Digital Di PT Nugraha Kreasi Digital - Siti Nurviatika; Setiawati (Riset Sinergi Indonesia (RISINDO), 2026)
The development of digital technology has driven the emergence of web-based health information platforms that are faster, more efficient, and easily accessible. This study aims to design and implement the HealthDoc website as a digital product that provides healthcare service information through a modern, responsive, and user-friendly interface. The benefits of this research include offering a web-based health information solution for companies and serving as a reference for frontend development using a UI/UX approach. The dataset used consists of company information content, healthcare service data, design assets from the UI/UX team, and visual prototypes created using Figma. The research employs a descriptive qualitative method with the Waterfall development model, covering stages such as requirements analysis, UI/UX design, implementation using HTML, Tailwind CSS, and JavaScript, as well as responsiveness and functionality testing using DevTools and the black-box method. The development process includes design slicing, structuring layouts using Tailwind CSS utility-first classes, adding interactivity with JavaScript, and deploying the website via Vercel to ensure stable online access. The results show that the HealthDoc website operates optimally across various devices, with all features functioning as intended and the interface aligning with the original design. Therefore, the HealthDoc website is effective as both a digital health information platform and a professional company profile